ILUSTRASI, INSPIRASI DAN KREASI GAMBAR PERUMAHAN BERWAWASAN LINGKUNGAN DENGAN PROGRAM 3D SKETCHUP - Subaidillah Fansuri; Anita Intan Nura Diana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
Housing is a place where a house is built in groups such as a good urban settlement which is equipped with facilities and infrastructure along with public utilities for livable houses. Many housing developments in Sumenep, but not in accordance with the existing Indonesian National Standard. The purpose of environmentally friendly housing is where the housing is in accordance with the provisions of the Indonesian national standard which concerns various aspects of housing planning. The large amount of open land in Sumenep Regency is an asset to the development of Sumenep Regency, whose population is increasing every year. Because of that, we need a program that will facilitate the public's understanding of buildings by construction implementers to conceptualize environmentally friendly housing. The program that will later be outlined in a settlement framework is the concept of a creation and inspiration of housing images with the 3D Sketchup program. Implementation by means of training or workshops on how to design environmentally friendly housing concepts with the 3D Sketchup program which later can be used as an implementation concept in implementing housing infrastructure development which will be carried out by construction implementers in Sumenep Regency.